Many particle and bandstructure effects in intersubband quantum well optics - Pereira Jr., M.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
In this paper, intersubband optical absorption spectra are computed from an optical susceptibility derived from the many-body formalism. The theory is valid for both non-equilibrium and equilibrium conditions. Numerical results are presented for III-V quantum wells at equilibrium, and electron subband nonparabolicity is partially taken into account by means of different effective masses, adjusted to non-parabolic bands calculated with a 8x8 k p Hamiltonian.